STRUCTURE ANALYSIS AND MULTI-OBJECTIVE OPTIMIZATION DESIGN OF A DEWATERING BUCKET FOR A PULSATOR WASHING MACHINE - CAI Yun; PENG Liang; LIU Xue; CHENG ZhiWen (Jixie qiangdu)
In order to suppress the vibration noise of a tumble dryer（ internal barrel） in a pulsator washing machine,and to optimize the internal barrel for better performance,firstly,a parameterized finite element model of the internal barrel was established by Solidworks software and imported into ANSYS Workbench software. After analyzing it and obtaining the main parameters that effect the performance of an internal barrel,the independent variables were decided for the structure optimization design of the internal barrel. Secondly,Design of Experiments and Response Surface Methodology were combined to solve a multi-objective optimization problem,under the condition of improved strength and stiffness,solution with the lightest mass is choosen as the optimization goal. Using Central Composite Design in ANSYS Workbench software,experimental points were selected,and the response surface model of an inner barrel was built. Goodness of fit evaluated the fit of the response surface model to experiment data and assessed optimization parameters,then obtained the optimal solution.. Finally,an internal barrel model was built using the optimized size. The results of its dynamic finite element analysis show that the strength and stiffness of the optimized inner barrel are improved,at the same time,its quality is reduced by 5% and its dynamic performance is improved. It provides a theoretical basis for a structure optimization design of the actual product.